Emerging roles of the brain's default network. - Mantini, D; Vanduffel, W (2013)
During periods of inactivity, global metabolism does not decrease in the brain, and small but consistent increases in activity occur in a specific set of regions called the "default network". Although much is known about the topological and connectional properties of the default network, its functions remain a matter of debate. Functional neuroimaging and electrophysiological studies have suggested two apparently contrasting functions for this network: spontaneous cognition and monitoring the environment. Spontaneous cognition, however, is by default situated in a given external context, an external milieu to which we align ourselves and which must be monitored. This review integrates recent literature suggesting that the two proposed functions of the default network functions need not to be mutually exclusive, and that spontaneous cognition and monitoring of the environment represent complementary instances of conscious experiences occurring during idle moments of daily life.